Pengaruh Disiplin Kerja Dan Motivasi Kerja Terhadap Kinerja Pegawai Dengan Pengembangan Karir Sebagai Variabel Intervening Pada Dinas Ketenagakerjaan Dan Transmigrasi Sijunjung - Rahma Septia Sari; Ramdani Bayu Putra; Nila Pratiwi; Hasmaynelis Fitri (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
This study aims to determine and analyze the influence of Work Discipline and Work Motivation on Employee Performance, with Career Development as an intervening variable at the Department of Manpower and Transmigration in Sijunjung. This research employs the Structural Equation Modeling (SEM) approach using SmartPLS 3.0 for analysis. The population and sample of this study consist of all employees at the Department of Manpower and Transmigration in Sijunjung.The findings indicate that Work Discipline has an insignificant effect on Career Development. Work Motivation has a positive and significant effect on Career Development. Work Discipline has a positive and significant effect on Employee Performance. Work Motivation has an insignificant effect on Employee Performance. Career Development has an insignificant effect on Employee Performance. Work Discipline has an insignificant effect on Employee Performance through Career Development. Work Motivation has an insignificant effect on Employee Performance through Career Development.